99mTc-Phy portal perfusion index imaging helps predict the severity of hepatitis B virus cirrhosis: a preliminary study. Issue 9 (September 2018) - Liu, Ning-Hu; Dong, Meng-Jie; Liu, Hao; Lu, Xi-Li; Tian, Dan; Zhang, Jun; Yang, Jun; Sun, Jun-Hui; Wu, Li-Hua; Bi, Jian-Li; Zhang, Bo
Abstract : Objective: The aim was to perform exploratory research on the application of technetium phytate ( 99m Tc-Phy) portal perfusion index (PPI) imaging in predicting the complications of hepatitis B cirrhosis and their severity. Patients and methods: A total of 65 hepatitis B cirrhosis patients were stratified, respectively, into three groups from classes A to C according to Child–Pugh scores and five groups from stages 1 to 5 according to the five-stage prognostic system. PPIs were compared and analyzed, respectively, among the three and five groups. The correlations between PPIs and major biochemical indices of liver function were also analyzed. One-way analysis of variance was used to compare the PPIs among the various groups and a nonparametric Spearman test was used to analyze the correlations between PPIs and various biochemical indices. Results: PPIs of the five groups decreased gradually from stage 1 to stage 5 (73.03±8.49, 52.96±16.22, 46.24±15.25, 29.99±17.36, and 11.50±6.37, respectively); with the exception of the difference between stages 2 and 3 ( P =0.252), the differences between the remaining groups were statistically significant ( P <0.05). The PPI showed positive correlations with serum total protein, serum albumin, and albumin/globulin results ( r =0.292, 0.559, 0.520, respectively; P <0.05), and negative correlations with serum globulin ( r =−0.366, P <0.05). Conclusion: Technetium phytate PPI could be a promising noninvasive and effective method for predicting the complications of hepatitis B cirrhosis and their severity; a lower PPI value indicates a higher severity of complications for hepatitis B cirrhosis patients. PPI can provide very meaningful reference data for clinical practice.